Implementasi Pembelajaran Kontekstual untuk Menanamkan Nilai Kebersihan pada Anak Usia Dini - Arif, Muchamad; Mau, Yasintha Bere (Program Studi Pendidikan Luar Sekolah, 2025)
Abstract: Instilling the value of environmental cleanliness in early childhood needs to be done through a concrete and fun approach so that the value can be understood and applied in everyday life. This study aims to describe the learning process, children's responses, and the challenges faced in learning activities with the theme of cleanliness through direct practice. This study uses a qualitative descriptive approach with data collection techniques through participatory observation, semi-structured interviews, and documentation. The subjects of the study were children in group B at a kindergarten in Indonesia. The results of the study showed that learning with the theme